Evaluating Consent Labs: prioritizing sexual wellbeing through a youth-led, curriculum-based education initiative - Kang, Melissa; Wan, Angelique; Cooper, Julia; Yu, Joyce (Frontiers in Education, 2024)
Introduction Consent Labs is an Australian, youth-led, not-for-profit organization delivering comprehensive consent education. Workshops are co-designed by young people and delivered by near-to-peer facilitators in secondary and tertiary institutions. The aims of this paper are (1) to describe the development, design and delivery of Consent Labs and (2) to conduct a retrospective analysis of evaluation data collected by Consent Labs. Methods E-survey data were collected by workshop facilitators between March 2021 and April 2023. This paper presents a retrospective analysis of these de-identified data. Survey items included age, identity, pre- and post- sexual consent knowledge, attitudes towards the content and delivery and questions inviting free-text responses. Quantitative data were analyzed using descriptive statistics: frequencies, self-reported change in knowledge using paired t-tests, and differences between groups using chi-square tests. Free-text responses were analyzed using content analysis. Results We describe the conceptualization of Consent Labs, present information about topics covered and report on process evaluation data analysis. Six thousand and twenty-six students returned complete evaluation surveys; 76.3% were school students and 23.7% were university students. The majority (67.3%) identified as female, 24.2% as male, 1.7% as non-binary, 1.2% as other gender identity. Self-reported change in knowledge before and after workshops was significant (pre-workshop knowledge mean score 3.77; post-workshop knowledge mean score 4.58; p < 0.0001). Change in knowledge remained significant when analyzed by institution, school type gender and sexual identity. ‘Consent Foundations’ was the most frequently selected (41.0%) topic as being most valuable. Respondents selected ‘Recognizing Coercion’ and ‘Gaslighting and Other Consent Challenges’ most frequently for future workshops (both 48.3%). Analysis of free text responses provided additional feedback. Discussion Consent Labs has been gaining recognition nationally since it was first implemented; this is the first analysis of process evaluation data. Limitations of the study include the low response rate, self-reported change in knowledge and the cross-sectional nature of the evaluation. Preliminary findings are encouraging and provide a sound platform for quality improvement and further evaluation. A recent government grant to partner with education academics will ensure that the Consent Labs program and continuing growth will be informed by more rigorous evaluation and evidence.